KURSI PUSAKA SEMINAR PROGRAM BOOK - Saiful Hairi, Othman (UNIMAS Publisher, 2024)
Kursi PUSAKA Seminar, organized by Institute of Creative Arts and Technology (iCreaTe), UNIMAS and Sarawak Timber Industry Development Corporation (STIDC), is a two-day event focusing on the R&D initiatives conducted by STIDC and UNIMAS, to provide valuable insights into the latest information on forest timber and non-timber forest products. With a lineup of expert speakers from various fields, this event is open to industry professionals, researchers, and students who are interested in expanding their knowledge and connecting with peers.